2021
DOI: 10.1007/s12020-021-02697-y
|View full text |Cite
|
Sign up to set email alerts
|

A potential impact of SARS-CoV-2 on pituitary glands and pituitary neuroendocrine tumors

Abstract: Introduction Angiotensin-converting enzyme 2 (ACE2) is the receptor of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The effects of SARS-CoV-2 on normal pituitary glands function or pituitary neuroendocrine tumors (PitNETs) have not yet been elucidated. Thus, the present study aimed to investigate the potential risks of SARS-CoV-2 infection on the impairment of pituitary glands and the development of PitNETs. Methods PitNETs tissues were obtained from 11… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…showed that ACTH levels were increased in patients with COVID-19 compared with healthy controls. By contrast, ACTH levels were within the normal range in all participants in our study 46 . The basal cortisol levels were also higher in patients with COVID-19 than in controls.…”
Section: Discussioncontrasting
confidence: 63%
“…showed that ACTH levels were increased in patients with COVID-19 compared with healthy controls. By contrast, ACTH levels were within the normal range in all participants in our study 46 . The basal cortisol levels were also higher in patients with COVID-19 than in controls.…”
Section: Discussioncontrasting
confidence: 63%
“… 10 11 Studies have shown ACE-2 receptor expression in gonadotrophs, lactotrophs, somatotrophs and corticotrophs, although in low levels, as well as TMPRSS2 pituitary expression. 12 13 This supports the possibility of direct COVID-19 infection of the pituitary, and may explain the event of pituitary apoplexy in more moderate COVID-19 illness as described in both this and other published case reports.…”
Section: Discussionsupporting
confidence: 89%
“… 14 Additionally, ACTH production has been shown to be increased during moderate COVID-19 infection, but significantly decreased in those who were critically unwell, despite no change in GH, TSH or LH/FSH in either group. 12 It is possible that HPA axis dysfunction may contribute to symptoms attributed to ‘Long COVID-19’ syndrome like fatigue and memory loss. 15 Although this consequence of COVID-19 infection is likely more common than acute vascular events, an assumption about the cause of hypocortisolism in these patients may lead to a delay in diagnosis of more serious pathologies, such as apoplexy in our presented case.…”
Section: Discussionmentioning
confidence: 99%
“…We searched PubMed on April 05, 2021, using the search terms (“novel coronavirus” OR “SARS-CoV2” OR “COVID-19”) AND (“neuroendocrine tumors” OR “neuroendocrine tumours” OR “neuroendocrine neoplasms” OR “neuroendocrine carcinomas” OR “carcinoids”) for articles in English that documented the COVID-19 in patients with NENs. Sixteen articles appeared, including three case reports, 12 recommendations or consensus statements and one only mini-series of four cases among a large thoracic cancers series 19 , 22 , 23 , 24 17 , 18 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%